Festivals and deterioration of aquatic environment: A case study of Idol immersion in Tapi River, India - Ujjania, N C; Multani, Azahar A; Mistry, Chaitali A; Patel, Mitali S (UIR PRESS, 2018)
In the civil society different festivals are celebrated, these are the integral part of human life and many of festivals are religious, seasonal change and culturally important. The present study elucidated environmental impact of Ganesh idol immersion on water quality of Tapi River and for this purpose water samples were collected during different durations (pre immersion, during immersion and post immersion) from selected sampling stations or idol immersion points of Tapi River. The important water quality parameters like pH, temperature, dissolved oxygen, free carbon dioxide, total hardness, total alkalinity, biological oxygen demand, chemical oxygen demand, oil & grease and total calcium were analysed for the study. Result shows that dissolved oxygen was depleted while remaining parameter were increased during the idol immersion and it was concluded that aquatic ecosystem of Tapi river was deteriorated and pollution and nutrient load were increased due to these religious activities. The celebration of festivals and these religious activities can’t stop but pollution can reduce to save the river.